1977
DOI: 10.1530/acta.0.0840795
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and Reproductive Repercussions of Immunization Against Progesterone and Oestradiol in Female Rats

Abstract: Mature female rats were immunized with BSA-conjugates of oestradiol17\g=b\-6-carboxymethyloxime or progesterone-11-hemisuccinate. Sera tested two months later at 1/2000 dilution bound 63.3 % \ m=+-\3.1 sem and 21.2% \ m=+-\ 2.3 of the homologous tritiated hormone (10 pg), -oestradiol-17\g=b\(Oe2) and progesterone (P), respectively. Rats immunized against Oe2 had a significantly longer oestrous cycle (8.2 days vs. 4.5 days in BSA-immunized rats), with a prolonged leukocytic phase. The cycle of rats immunized ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

1981
1981
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
1
5
0
3
Order By: Relevance
“…Both these effects are modified by genotype. These data support the results of earlier experiments (Raziano et al, 1972;Csapo et al, 1975;French, 1977;Kaushansky et al, 1977;Elsaesser, 1980;Rider etal, 1986Rider etal, , 1987.…”
Section: Antibodies Against Progesteronesupporting
confidence: 91%
See 1 more Smart Citation
“…Both these effects are modified by genotype. These data support the results of earlier experiments (Raziano et al, 1972;Csapo et al, 1975;French, 1977;Kaushansky et al, 1977;Elsaesser, 1980;Rider etal, 1986Rider etal, , 1987.…”
Section: Antibodies Against Progesteronesupporting
confidence: 91%
“…Although immunization against oestrogens has infertility effects by blocking or delaying ovulation in most animals of a variety of species, there are reports demonstrating that in some immunized animals the ovulation rate and the litter size are normal or increased due, in part, to higher twining rate (Csapo et al, 1975;Kaushansky et al, 1977;Smith et al, 1981;Land et al, 1982;Sreenan, 1984). Even animals of the same species may respond differently to treatment with antibody against oestrogen (Martin et al, 1978;Wise and Schanbacher, 1983).…”
Section: Effects Of Immunization On Hypothalamo-pituitary-gonadal Relmentioning
confidence: 99%
“…Contrary to the increased ovulation rate noted in sheep immunized against oestrogens (Smith et ai, 1981) and the anovulatory response noted by Martin et ai (1978) (Ferin et ai, 1974;Hillier, Groom, Boyns & Cameron, 1975) and animals immunized against oestradiol can still maintain pregnancy (Ferin, Raziano, Tempone & Vande Wiele, 1970 ;Csapo, Dray & Erdos, 1975 ;Kaushansky, Bauminger, Koch & Linder, 1977;Nieschlag & Wickings, 1978). Oestrogens have been reported to be higher in animals with higher titres in that they may be unavailable for clearance (Sundaram et ai, 1973) or ovarian output of oestrogens is increased because of decreased feedback effects on gonadotrophins (Pantera/., 1978;Rawlings et ai, 1978;Martensz et ai, 1979;Scaramuzzi, Martensz & Van Look, 1980b …”
Section: Characterization Of the Antiserummentioning
confidence: 91%
“…As a result, progesterone antibodies can interfere with pregnancy. Active immunization with progester¬ one-bovine serum albumin (BSA) conjugate in¬ duces high levels of progesterone antibodies in the circulation and blocks pregnancy in rats (Kaushansky, Bauminger, Kock & Linder, 1977) and rabbits (Elsaesser, 1980). A series of studies with a mouse IgGl monoclonal antibody (DB3) against progester¬ one has shown that passive immunization shortly after mating prevents the onset of implantation in mice (Wright, Feinstein, Heap et al 1982), rats (Phillips, Hahn, McGuire et al 1988) and ferrets .…”
Section: Introductionmentioning
confidence: 99%